Antioxidant Activities of Fermented Soybean Prepared with Bacillus subtilis - He*, Shenghua; Ma, Ying; Zhou, Sanjiu; Song, Wei; Wang, Rongchun (Asian Journal of Chemistry, 2013)
The antioxidant activities of methanolic extract of fermented soybean prepared with Bacillus subtilis and cooked non-fermented soybean were investigated. The total phenolics increased markedly from 675 to 6629 mg/kg after 72 h of the fermentation time. At the same concentration level of lyophilized extract, soybean fermentation prepared with Bacillus subtilis showed a higher antioxidant activity than that cooked non-fermented soybean. Methanolic extracts of soybean fermentation prepared with Bacillus subtilis showed a higher reducing activity than that of cooked non-fermented soybean at the same concentration level of lyophilized extract. Ferrous ion chelating ability of methanol extracts from fermented soybean increased with the increase of the fermentation time. Soybean fermentation prepared with Bacillus subtilis showed a higher ferrous ion chelating ability than that of cooked non-fermented soybean at the same concentration level of lyophilized extract. Therefore, soybean preparation with Bacillus subtilis may be exploited as a functional food to alleviate oxidative stress.